Aerosol measurements during OASIS Barrow field intensive Spring 2009 (Arctic Data Center, 2016)
The NCAR "Particle Size Distribution" (PSD) instrument consists of three instruments that measure the size distribution of the ambient aerosol from 3 nm to 2 microns. General specifications for the instrument during Ocean-Atmosphere-Sea Ice-Snowpack (OASIS) are as follows: * Size range: ~3.85 nm to 2 micron * Number of diameter bins: 75 * Time resolution: 5 min Please see included documentation for full details.